The Psychology of Money: Pelajaran Abadi Mengenai Kekayaan, Ketamakan, dan Kebahagiaan - Ayu Safitri; Putri Rizky Apriyani; Shen Fuwi (Literaksi: Jurnal Manajemen Pendidikan, 2024)
This study aims to review the contents of a book entitled "The Psychology of Money: Timeless Lessons About Wealth, Greed, and Happiness" as an effort to study and examine the contents of the book. This research using a qualitative descriptive method looks at the simple way to get rich, and the right mindset about money with a qualitative approach. This study contains a content analysis of the book above. The data sources used by the author are data sources obtained from various types of articles, journals, and books that are still related to the object under study. This book is a self-development themed book. In this book it is said that a person uses money well not because he has good knowledge about money, but because he behaves properly when using money. This book teaches readers about the right way when we make decisions about money. There are 19 stories that present various strange people in making decisions related to money.